The Prognostic Value of Hyponatremia for Predicting Poor Outcome in Patients With COVID-19: A Systematic Review and Meta-Analysis - Akbar, Mohammad Rizki; Pranata, Raymond; Wibowo, Arief; Irvan,; Sihite, Teddy Arnold; Martha, Januar Wibawa (Frontiers in Medicine, 2021)
Background This meta-analysis aimed to assess the prognostic value of hyponatremia in patients with COVID-19. Methods We performed a systematic literature search on PubMed, Scopus, ScienceDirect, and Wiley up until 26 January 2021. The key exposure was hyponatremia, defined as sodium level below the reference level. The outcome of interest was poor outcome, which was a composite of mortality, severe COVID-19, and prolonged hospitalization. Severe COVID-19 was defined severe CAP or needing ICU care or IMV. The pooled effect estimate was odds ratio (OR). Sensitivity, specificity, positive and negative likelihood ratio (PLR & NLR), diagnostic odds ratio (DOR), and area under curve (AUC) were generated. Results There were 11,493 patients from 8 studies included in this systematic review and meta-analysis. The incidence of hyponatremia was 24% and incidence of poor outcome was 20%. Hyponatremia was associated with poor outcome in COVID-19 (OR 2.65 [1.89, 3.72], p<0.001; I2: 67.2%). Meta-regression analysis showed that the association between hyponatremia and poor outcome was reduced by age (OR 0.94 [0.90, 0.98], p=0.006) and hypertension (OR 0.96 [0.93, 0.94], p<0.001). Hyponatremia has a sensitivity of 0.37 [0.27, 0.48], specificity of 0.82 [0.72, 0.88], PLR of 2.0 [1.5, 2.7], NLR of 0.77 [0.69, 0.87], DOR of 3 [2, 4], and AUC of 0.62 [0.58, 0.66] for predicting poor outcome. In this pooled analysis, hyponatremia has a 33% post-test probability for poor outcome, and absence of hyponatremia confers to a 16% post-test probability. Conclusion Hyponatremia was associated with poor outcome in patients with COVID-19 PROSPERO: CRD42021233592